G278(P) Predictive value of persistent NS1 antigen positivity for dengue haemorrhagic fever. (May 2019) - Manamperi, DMM; Jayamanne, D; Somaratne, T; Perera, N; Wijesinghe, MAHU; Fernando, AJAL
Abstract : Background: Dengue haemorrhagic fever (DHF) is a major public health concern responsible for significant morbidity in both adult and paediatric populations in Sri Lanka. The detection of non-structural protein 1 (NS1) antigen in the serum at the early stage of the disease is effective in diagnosing dengue infection. This has been assessed and proven in the past. However, very few studies have correlated persistent antigen positivity with the disease severity. Moreover, there is a general assumption that if there is a high viral load the NS1 will remain positive for longer and DHF is more likely. Aims: This study examined if persistent NS1 antigen positivity beyond day 3 of a patient infected with dengue virus was predictive of the occurrence of dengue haemorrhagic fever, which is considered as the more severe disease. Methods: This is a prospective analysis of NS1 antigen positive patients admitted to a General Paediatric ward and a specialised centre for clinical management of dengue in Sri Lanka from 1 st of January 2017 to 31 st of December 2017. All consenting NS1 antigen positive patients diagnosed during the first 2 days of fever were included. The patients were followed up during their in-hospital stay and the severity of the illness was classified according to the WHO classification. The NS1 antigen test was repeated after day three of the onset of illness, at least 2 days after the initial test. Ethical clearance was obtained from the ethical review committee of Sri Lanka College of Paediatricians Results: One hundred and fifty-seven patients were enrolled. Persistent NS1 antigen test positivity after day 3 of the illness was not predictive of subsequent development of DHF. However, these are not the expected results by the investigators, based on previously published studies. Out of multiple other demographic and illness-related factors assessed, only having a secondary dengue infection was associated with a high risk of DHF (RR=3.077, 95% CI 1.361, 6.954) Conclusion: Persistent NS1 positivity on day three and beyond may not be indicative of disease severity. However, results need to be confirmed by a larger study with quantitative NS1 testing.